Earmarking Tobacco Taxes for Health Purposes via Median Entities - Michael Igoumenidis; Kostas Athanasakis (Kerman University of Medical Sciences, 2014)
Fiscal policies are an especially promising lever for reducing the burden of non-communicable diseases and injuries (1). On World No Tobacco Day 2014, World Health Organization (WHO) repeated with greater intensity its well-known proposal (2) on raising tobacco taxes to encourage users to stop or reduce consumption, and to prevent potential users from taking up smoking. Evidence as to why this is an effective strategy abounds (3). Despite concerns over manufacturers' political influence, technical problems such as tax manipulation, and increased smuggling considerations, it is hoped that governments shall be scaling their efforts toward this direction in the next few years, by enforcing increases in specific excise taxes. A 2011 review of more than 100 econometric studies estimates that doubling inflation-adjusted prices should reduce consumption by about one third (4). In terms of revenue, WHO estimates that raising specific excise taxes on tobacco to double prices would raise about 100 billion US dollars per year worldwide, in addition to the approximately 300 billion US dollars that governments already collect on tobacco (5). Each country enforcing such taxes must decide how to allocate their share of this prospective additional revenue in advance. Careful consideration is particularly important; this is a chance for tobacco to atone, partly at least, for the damage it has inflicted throughout the years of its uncontrollable use.